Role of data literacy training for decision-making in teaching practice: a systematic review - Sandoval-Ríos, Fabián; Gajardo-Poblete, Carla; López-Núñez, Juan Antonio (Frontiers in Education, 2025)
This systematic review examines the impact of data literacy training on teachers’ and pre-service teachers’ decision-making skills. Data literacy, essential for effective teaching, involves formulating questions, collecting relevant data, and making informed decisions. The review analyzed 16 studies published between 2014 and 2023, selected from Web of Science, Scopus, and EBSCOhost. Findings indicate that structured decision-making models, authentic contexts, collaborative learning, and long-term follow-up are the most effective strategies, leading to significant improvements in self-efficacy and knowledge. Programs emphasizing real-world data applications and structured instructional support had the greatest impact on teachers’ confidence and ability to use data for pedagogical decision-making. However, a gap remains in explicitly fostering decision-making skills, as many studies prioritized data analysis over instructional application. These results highlight the need for training programs that integrate structured decision-making into data literacy frameworks, ensuring teachers not only analyze data but also apply it effectively. Future research should focus on developing standardized assessment tools and conducting long-term studies to evaluate the lasting impact of data literacy training on teaching practices.